Nurse Staffing Factors, Fatigue, and Work-related Stress among Emergency Department Nurses During COVID-19 Pandemic - Ferdy Lainsamputty; Ailine Yoan Sanger; Ni Made Dewi Susanti; Christanti Indriani Pontoh (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aims : This study aimed to examine the relationship between nurse staffing factors, fatigue, and stress among emergency department (ED) nurses during pandemic. Design : Descriptive, correlation, and cross sectional approach. Methods : Using cross-sectional design, a total of 113 ED nurses in Indonesia selected by convenience sampling completed the survey on the Fatigue Severity Scale (FSS) and the Expanded Nursing Stress Scale (ENSS). Data analysis included descriptive statistics and bivariate analysis. Results : Nurse staffing factors were not significantly associated with stress (r = -0.07-0.16, p > 0.05). Fatigue correlated with the domain of death and dying (r = 0.19, p < 0.05), problems relating to supervisors (r = 0.19, p < 0.05), workload (r = 0.26, p < 0.01) and patients/families (r = 0.25, p < 0.01), and overall stress (r = 0.21, p < 0.05). Conclusions : The more severe fatigue the emergency nurses suffered, the worse stress they experienced. The workload and rotation of nurses during pandemic should be readjusted in accordance with current hospital situation. Identification of basic needs during the pandemic such as ensuring the supply of personal protective equipment (PPE) may help to reduce stress and to maintain the service quality in ED. Organizing counseling programs and support group through online meetings can help nurses to share their difficulties and experiences and to prevent them from feeling isolated.